SYSTEMATIC ANALYSIS AND OPTIMIZATION OF MOBILE MACHINE FLUCTUATIONS - N. N. Hurski; Y. I. Slabko; R. I. Fourounjiev; A. L. Homich (Наука и техника)
The paper considers a calculated scheme of three-dimensional fluctuations of a multi-prop machine. Equations of the mobile machine movement are given in the paper. Then paper contains static and power analyses of the mobile machine fluctuations and also parametrical optimization.